The Relationship of Geopolitical Risk and Tourism in Turkey: Fourier Toda-Yamamoto Causes Analysis - Esra Soyu Yıldırım (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2023)
Economic growth is fueled by the tourism industry, which is crucial for emerging nations. The risk variables that can have an impact on the tourism industry, which has a very delicate structure, must be looked into. Researching the link between geopolitical risk and tourism has become necessary, especially in Turkey, where geopolitical tensions are at their highest. The study's objective is to investigate the connection between geopolitical risk and tourism in the context of Turkey. With the aid of the Fourier Toda-Yamamoto (TY) causality test and the Fractional Fourier Toda Yamamoto causality test, the relationship between the number of tourists, geopolitical risk, Brent oil, real effective exchange rate, and CPI in Turkey during the 2003:02-2021:01 period was examined in this study. The Fourier TY causality test revealed a causal relationship between BRENT and CPI variables and TS variables, as well as a causal relationship between TS variables and BRENT variables and a causal relationship between REER variables and CPI variables. Additionally, it can be observed that there is a causative relationship between BRENT and CPI and TS, as well as between TS and BRENT and CPI, according to the findings of the Fractional Fourier TY causality test used to determine whether the shocks are permanent. In addition, there is a one-way causality relationship from REER to CPI. The results show that the shocks are permanent. Based on the literature reviewed, while geopolitical risks are expected to negatively affect the number of tourists, no causal relationship could be found between geopolitical risks and the number of tourists in the case of Turkey.